2014
DOI: 10.1212/wnl.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Satiety-related hormonal dysregulation in behavioral variant frontotemporal dementia

Abstract: Despite a tendency to overeat, patients with bvFTD have a hormonal profile that should decrease food intake. Aberrant hormone levels may represent a compensatory response to the behavioral or neuroanatomical abnormalities of bvFTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Despite the recognized role of the hypothalamus in eating behavior, only one study has investigated the possible role of the hypothalamus in FTD and showed atrophy of the posterior hypothalamus in FTD patients [64]. Interestingly, Woolley et al [65] recently published a study showing an association between overeating and an anorexigenic hormonal profile in bvFTD patients, which is consistent with the satiety acknowledged by patients and can be interpreted as a compensatory mechanism. At late stages of the disease, these changes can evolve toward hyperorality.…”
Section: The Ftd Symptoms and Corresponding Tests In Micementioning
confidence: 90%
“…Despite the recognized role of the hypothalamus in eating behavior, only one study has investigated the possible role of the hypothalamus in FTD and showed atrophy of the posterior hypothalamus in FTD patients [64]. Interestingly, Woolley et al [65] recently published a study showing an association between overeating and an anorexigenic hormonal profile in bvFTD patients, which is consistent with the satiety acknowledged by patients and can be interpreted as a compensatory mechanism. At late stages of the disease, these changes can evolve toward hyperorality.…”
Section: The Ftd Symptoms and Corresponding Tests In Micementioning
confidence: 90%
“…Decreased ghrelin and cortisol levels, as well as high insulin levels, have been previously reported in bvFTD. 5 Insulin levels, however, were not related to BMI, which could reflect a state of insulin resistance and metabolic change, 4 rather than a role in controlling satiety. High leptin levels were also observed in a small subset of patients with bvFTD (n 5 5) who overate.…”
mentioning
confidence: 93%
“…High leptin levels were also observed in a small subset of patients with bvFTD (n 5 5) who overate. 5 Another study failed to find significant differences in leptin levels between patients with FTD and those with AD dementia, although the authors suggested that hyperphagic females with FTD may have higher leptin levels. 23 This finding seems paradoxical to the eating behaviors seen in bvFTD, as leptin inhibits food intake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Appetite-regulating peptide levels in subjects with bvFTD are found to be consistent with an expected satiated state between meals [18, 32, 33]. Appetite-regulating peptide levels differ between subjects with bvFTD and healthy controls.…”
Section: Frontotemporal Lobar Degenerationmentioning
confidence: 96%